Enhancement of Plain Carbon Steels Corrosion by Heat Treatment of the Direct Electrodeposited Ni-P-SiC Deposit - Abdulsalam H. Salamah,; Mohammed A. Almadani,; Salah A. Gnefid, (AlQalam Journal of Medical and Applied Sciences, 2024)
The current study examined the effects of heat treatment on the microhardness and wear resistance of electrodeposited Ni-P-SiC coatings, as well as the effects of SiC particle concentrations on the coating's metallic continuous phase. Direct electrodeposition onto a low alloy steel electrode (0.40 C) was used to obtain the deposits. A modified Watt bath and pure nickel anode were used, and the material was heat treated for one hour at 400 °C. Using XRD and SEM methods, the Ni-P-SiC deposit was characterized. Additionally, the deposit's microhardness was assessed using the LECO, DM-400, both before and after heat treatment, with a 50g load. The results obtained indicate that the coating's deposition on the surface of low alloy steel and its impacts on the deposit coating crystal plane may be influenced by the applied current density. The SiC dispersion slightly improved as the bath's SiC content rose. The reduction in phosphor content of the deposited Ni-P-SiC coating as a result of the SiC particles being added to the Ni-P electrodeposition bath. The XRD data showed that crystalline Ni and Ni3P are formed as a result of the heat treatment procedure. As the SiC content in the electrodeposition bath and heat treatment procedure rises, so does the microhardness of the Ni-P-SiC deposit. Low alloy steel's resistance to erosion corrosion can be strengthened by the Ni-P-SiC. تناولت الدراسة الحالية تأثيرات المعالجة الحرارية على الصلادة الدقيقة ومقاومة التآكل لطلاءات النيكل - الفوسفور - كربيد السيليكون والمترسبة كهربائياً، بالإضافة إلى تأثيرات تركيزات جسيمات كربيد السيليكون فى الطور المعدني المستمر للطلاء. تم استخدام التفريغ الكهربائي المباشر على قطب فولاذي منخفض السبائك (0.40 درجة مئوية) للحصول على الرواسب. تم استخدام حمام وات معدل وأنود النيكل النقي، وتمت معالجة المادة بالحرارة لمدة ساعة واحدة عند 400 درجة مئوية. باستخدام طرق حيود الأشعة السينية والمجهر الماسح الألكتروني، تم تقييم الصلادة الدقيقة للرواسب باستخدام جهاز الليكو، دي أم-400، قبل وبعد المعالجة الحرارية، بحمل 50 جم. تشير النتائج التي تم الحصول عليها إلى أن ترسب الطلاء على سطح الفولاذ منخفض السبائك وتأثيراته على المستوى البلوري لطلاء الرواسب قد يتأثر بكثافة التيار المطبقة. تحسن توزيع جسيمات كربيدات السليكون قليلاً مع زيادة محتواها في محلول النيكل-فسفور في عملية الترسيب الكهربائي. أظهرت نتائج حيود الأشعة السينية أن التركيب البلوري للنيكل وفوسفايد النيكل الثلاثي يتشكلان نتيجة لإجراء المعالجة الحرارية. مع ارتفاع محتوى كربيد السيليكون وإجراءات المعالجة الحرارية، ترتفع أيضًا الصلابة الدقيقة لرواسب النيكل - الفوسفور - كربيد السيليكون. وتخلص الدراسة الى أنه يمكن تعزيز مقاومة سبائك الفولاذ المنخفض الكربون للتآكل بواسطة الترسيب الكهربائي المباشر لطلاءات النيكل - الفوسفور - كربيد السيليكون